A flexible pressure responsive device based on the interaction between silver nanoparticles and an aluminum reflector. (4th December 2017) - Rankin, Alasdair; McGarry, Steven
Abstract: The unique and tunable optical properties of metal nanoparticles have attracted intense and sustained academic attention in recent years. In tandem with the demand for low-cost responsive materials, one particular topic of interest is the development of mechanically responsive device structures. This work describes the design, fabrication, and testing of a mechanically responsive plasmonic device structure that has been integrated onto a standard commercial plastic substrate. With a low actuation force and a visually perceivable color shift, this device would be attractive for applications requiring responsive features that can be activated by the human hand.